2016
DOI: 10.1159/000449431
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of 5S rDNA and Recurrent Association of Transposable Elements in Electric Fish of the Family Gymnotidae (Gymnotiformes): The Case of <b><i>Gymnotus mamiraua</i></b>

Abstract: Gymnotidae is a family of electric fish endemic to the Neotropics consisting of 2 genera: Electrophorus and Gymnotus. The genus Gymnotus is widely distributed and is found in all of the major Brazilian river systems. Physical and molecular mapping data for the ribosomal DNA (rDNA) in this genus are still scarce, with its chromosomal location known in only 11 species. As other species of Gymnotus with 2n = 54 chromosomes from the Paraná-Paraguay basin, G. mamiraua was found to have a large number of 5S rDNA sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…On the top of that, some authors [64, 65] found a unique class of SINEs that have been formed by fusion of a 5S rRNA gene and a LINE, showing that 5S and retroelements may interact. In support, SINE elements with 5S features were reported in several fish [54, 64] and a retroelement was co-localised with 5S loci on Erythrinus erythrinus (red wolf fish) chromosomes [19] and recently among members of another fish genus, Gymnotus [66]. In the future it will be interesting to analyse inter-block spacers in Group II reads (those containing one or few blocks of 5S genes head to tail, plus unrelated sequences) for the presence of transposable elements which may support their potential role in 5S rDNA mobilisation.…”
Section: Discussionmentioning
confidence: 80%
“…On the top of that, some authors [64, 65] found a unique class of SINEs that have been formed by fusion of a 5S rRNA gene and a LINE, showing that 5S and retroelements may interact. In support, SINE elements with 5S features were reported in several fish [54, 64] and a retroelement was co-localised with 5S loci on Erythrinus erythrinus (red wolf fish) chromosomes [19] and recently among members of another fish genus, Gymnotus [66]. In the future it will be interesting to analyse inter-block spacers in Group II reads (those containing one or few blocks of 5S genes head to tail, plus unrelated sequences) for the presence of transposable elements which may support their potential role in 5S rDNA mobilisation.…”
Section: Discussionmentioning
confidence: 80%
“…The Gymnotiformes order has considerable variation, not only in diploid number (from 2 n = 24 in Apteronotus albifrons , Howell, 1972 ; Almeida-Toledo et al, 1981 ; Mendes et al, 2012 ; to 2 n = 74 in Rhabdolichops cf eastward , Suárez et al, 2017 ) but also in the karyotype formula and location of repetitive sequences (Fernandes et al, 2005 ; Almeida-Toledo et al, 2007 ; Silva et al, 2009 ; da Silva et al, 2013 ; Jesus et al, 2016 ; Araya-Jaime et al, 2017 ; Batista et al, 2017 ; Sousa et al, 2017 ; Takagui et al, 2017 ). Recently, fluorescence in situ hybridization (FISH), has played an important role in understanding the genome structure of fish species (Yi et al, 2003 ; Cabral-de-Mello and Martins, 2010 ; Martins et al, 2011 ; Vicari et al, 2011 ; Gornung, 2013 ; Knytl et al, 2013 ; Yano et al, 2017 ) and molecular cytogenetic studies in Gymnotiformes have shown dynamic reorganization, including pericentric inversions observed through repetitive DNA position (Fernandes et al, 2017 ), sequence dispersion via transposable elements and the association between different repetitive sequences (Utsunomia et al, 2014 ; da Silva et al, 2016 ; Machado et al, 2017 ) and the presence of different sex chromosome systems (Margarido et al, 2007 ; Henning et al, 2008 , 2011 ; da Silva et al, 2011 , 2014 ; Almeida et al, 2015 ). This evolutionary plasticity of the karyotype is seen in Gymnotus (Table 1 ), a genus that has high interspecific variability in chromosome numbers (Figure 1 , Table 1 ), ranging from 2 n = 34 in Gymnotus capanema (Milhomem et al, 2012a ) to 2 n = 54 in G. carapo (Foresti et al, 1984 ), G. mamiraua (Milhomem et al, 2007 ), G. paraguensis (Margarido et al, 2007 ) and G. inaequilabiatus (Scacchetti et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In other species several TEs or considerable parts of them were observed within NTS regions. For example, SINEs were noticed in fish and grasshoppers (Nakajima et al, 2012;Merlo et al, 2012Merlo et al, , 2013da Silva et al, 2011da Silva et al, , 2016Bueno et al, 2016). Because no putative TEs were identified by our analysis, the dispersion of 5S rDNA might occur via other mechanisms, such as ectopic recombination.…”
Section: Discussionmentioning
confidence: 82%
“…The genome plasticity of 5S rDNA sequences at the chromosomal and molecular level is known, including the unique or multiple clusters and their association with TEs (da Silva et al, 2011(da Silva et al, , 2016Nakajima et al, 2012;Merlo et al, 2013;Bueno et al, 2016), other multigene families (Eirín-López et al, 2004;Cabral-de-Mello et al, 2011b;Vierna et al, 2011), as well their potential to generate satDNA (see for example Gatto et al, 2016). The presence of scattered 5S rDNA signals in C. armatus chromosomes is uncommon.…”
Section: Discussionmentioning
confidence: 99%